Frequency distribution and potence ratio of agronomic traits in F1 generation of intraspecific crosses of Robusta coffee. - Ari Wibowo; Ucu Sumirat (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Leaf morphological traits and internode length significantly affect the adapt-ability and production of coffee plants, respectively. Therefore, genetic studies of these two characters can support the effectiveness of Robusta coffee breeding program for obtaining superior planting materials. This study aimed to determine the diversity and frequency distribution of F1 generation on internode length and leaf size of Robusta coffee crosses. The study involved six groups of F1 progeny and their reciprocals (F1R) resulted from a cross of three parents, namely BP 961, Q 121, and BP 409. Each cross combination was planted with 41–49 progenies singly side by side in Kaliwining Experimental Station, Jember, Indonesia. The observed traits were internode length and leaf size. Analysis results of progeny variation distribution showed that most of the F1 and F1R progenies from intraspecific Robusta crosses had shorter branches than both parents in all combinations of crosses, even in BP 961 × BP 409 crosses. In addition, all F1 and F1R progenies had shorter internodes than both parents. More than 50% of the progeny of Q 121 × BP 409 and BP 961 × BP 409 crosses showed leaf length trait between parents. This indicates the absence of dominance of one parent in the progeny. Less than 20.9% of the progeny had a narrower leaf size than Q 121 parent. Most of the F1 and F1R crosses had a leaf width between both parents. The leaf length and leaf width traits were incomplete dominance or recessive, while the internodelength was overdominant.